PHENOMENOLOGY OF MERLEAU-PONTY PERCEPTION FOR THE EXPERIENCE OF SEXUAL VIOLENCE SURVIVORS - TRIGUSWINRI, KRISNALDO; HADITA, CYNTHIA (Universitas Islam Lamongan, 2022)
If perception is the point of the human experience, then bodily experience is where the perception begins. The perception shows that human is global: being-in-the-world. By understanding perception as the intensity of our entire way of being in this world, the human body must be understood as body-subject and not body-object. In his philosophical thinking, Merleau-Ponty defines the human body not against inanimate things or objects in the world, but as a living body. Due to it being alive and containing intelligence, our bodies interact actively and intelligently with their environment. Therefore, the writer wants to see the intersection between perceptions, body subjects, and bodily experiences of survivors of sexual violence. This study used an approach with the data collection techniques in the form of literature. Through the rigidity in conducting the analysis, the writer found the problem of sexual violence parallels with the concept of perception and bodily experience that was encouraged by Merleau-Ponty.